Security challenges in cognitive radio network and defending against Byzantine attack: a survey. (2016) - Kar, Sumit; Sethi, Srinivas; Bhuyan, Manmath Kumar
Wireless applications have been growing rapidly in the past years, leading to the problem of spectrum scarcity. Cognitive radio network (CRN) is an emerging technology which can provide a promising solution to resolve this spectrum scarcity problem in wireless communication. However, the security concerns in cognitive radio (CR) is an unavoidable issue, since it introduces significant new classes of threats due to its unique characteristics and functioning techniques and also has received more attention by the researchers recently. In this paper, we provide a brief overview of CRN technology and analyse its associated security vulnerabilities and discuss a number of available solutions for countering those threats. We identify the security threats based on the targeted open system interconnection (OSI) layer and classified those into traditional wireless threats and CRN specific threats. The paper will also focus on Byzantine attack or spectrum sensing data falsification (SSDF) attack, which is a common CRN specific threat and reviewed the distinguished proposed techniques by research community to detect and isolation of such attack. Finally, a road-map for future research is addressed.